2010
DOI: 10.1142/s0218271810018219
|View full text |Cite
|
Sign up to set email alerts
|

Interferometer Response to Scalar Gravitational Waves

Abstract: It was recently suggested that the magnetic component of Gravitational Waves (GWs) is relevant in the evaluation of frequency response functions of gravitational interferometers. In this paper we extend the analysis to the magnetic component of the scalar mode of GWs which arise from scalar-tensor gravity theory. In the low-frequency approximation, the response function of ground-based interferometers is calculated. The angular dependence of the electric and magnetic contributions to the response function is d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…In fact, the so-called magnetic components of GWs have to be taken into account in the context of the total response functions of interferometers for GWs propagating from arbitrary directions, [7,[40][41][42][43][44]. In a recent paper, the magnetic component has been extended to GWs arising from STG too [45]. In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the so-called magnetic components of GWs have to be taken into account in the context of the total response functions of interferometers for GWs propagating from arbitrary directions, [7,[40][41][42][43][44]. In a recent paper, the magnetic component has been extended to GWs arising from STG too [45]. In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in Ref. [45] it has been shown that if one neglects the magnetic contribution considering only the low-frequency approximation of the electric contribution, an important portion of the signal could be, in principle, lost in the case of STG too, in total analogy with the standard case of GTR [7,[40][41][42][43][44]. Then, it is clear that the computation of a more precise response function for the magnetic contribution is important also in the framework of the possibility of distinguishing other gravitational theories from GTR.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations